Area strain predicts clinical course in patients with heart failure with midrange ejection fraction. (14th October 2021) - Tunyan, L.G; Chilingaryan, A; Sisakyan, J.G; Tumasyan, L.R; Kzhdryan, H.K; Zelveyan, P.H
Abstract: : Heart failure with midrange ejection fraction (HFmrEF) as a relatively new category remains understudied. Some studies have shown that patients with HFmrEF more resemble to those with heart failure with reduced ejection fraction (HFrEF), but many patients with HFmrEF are able to improve their EF to preserved one. The transformation course is hard to predict. We assumed that novel strain parameters might predict this transformation. Methods: 73 patients with HFmrEF NYHA II-III, 62±5 years (32 female) on optimal medical therapy and 43 age and sex matched healthy controls were involved in the study. Global values of longitudinal (GLS), circumferential (GCS) and radial strain (GRS), left ventricular torsion (LVT), peak LV twist (LVTR) and untwist rates (LVUTR), and area strain (AS) were measured by 2D/3D echocardiography and analyzed offline by one experienced specialist. All measurements were done at the study onset and in 1 year follow up. Results: Patients with HFmrEF had significantly lower absolute values of GLS, GCS, GRS, LVT, LVTR, LVUTR and AS compared with controls. In one year follow up 24 (37%) patients with HFmrEF moved into HFrEF category and 14 (19%) moved up to HFpEF and the rest of the patients remained in HFmrEF group. Patients with HFrEF had significantly lower absolute values of AS, LVT, LVTR and LVUTR compared with patients who remained in HFmrEF group and patients that moved to HFpEF category, whereas patients with HFpEF had greated absolute values of GRS, AS and LVT, and without differences in LVTR and LVUTR compared with patients with HFmrEF. (HFrEF AS: −16.31±3.21% vs −22.34±6.31%, p<0.01; LVT: 0.72±0.13°/cm vs 1.12±0.42°/cm, p<0.03; LVTR 29.31±11.23°/s vs 48.32±19.71°/s, p<0.03; LVUTR 25.33±12.41°/s vs 49.23±18.34°/s, p<0.03; HFpEF AS: −31.23±4.35% vs −23.34±6.31%, p<0.01; LVT: 1.93±0.13°/cm vs 1.12±0.42°/cm, p<0.03; LVTR 41.62±15.81°/s vs 48.32±19.72°/s, p=0.08; LVUTR 41.41±16.72°/s vs 49.22±18.31°/s, p=0.12, GRS 45.34±7.41% vs 29.42±5.81%, p<0.002). Patients with subsequent HFrEF transformation also had lower AS values at beseline (−17.31±4.21% vs −24.21±6.83%, p<0.002). AS was the only predictor of HFmEF transformation into HFrEF or HFpEF with cut off values −17.1% and −32.7% respectively, (area under the curve 0.834) Conclusion: Patients with HFrEF move into HFrEF category more frequently than into HFpEF. AS predicts transformation of HFmEF into HFrEF or HFpEF. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): City Hall resources